Chagas disease, a risk factor for high blood pressure. (December 2014) - Vicco, Miguel Hernán; Rodeles, Luz; Yódice, Agustina; Marcipar, Iván
Abstract Background. Chagas disease is a parasite infection caused by the protozoan Trypanosoma cruzi. Its most common complications is chronic Chagas heart disease but impairments of the systemic vasculature also has been observed. Although the different mechanisms that regulate blood pressure are disrupted, to our knowledge data on the association of hypertension and chronic Chagas disease are scarce. In this regard we evaluate whether Chagas disease constitutes a high blood pressure risk factor. Materials and methods. We recruited 200 individuals, half of them with positive serology for T. cruzi. They were subjected to a complete clinical examination. Results. The mean age of sampled individuals was 46.7 ± 12.3, and the mean of systolic and diastolic blood pressure were 124 ± 12 mmHg and 82 ± 10 mmHg, respectively. There were no between-group differences regarding age, sex distribution or body mass index. Chagas disease contributed significantly to high blood pressure (OR = 4, 95% CI 1.8323–7.0864, p = 0.0002). Conclusion. Our results reveal an important association between Chagas disease and high blood pressure, which should be contemplated by physicians in order to promote preventive cardiovascular actions in patients with Chagas disease.